PENGARUH KADAR HB DENGAN LAMA PENGELUARAN PLASENTA PADA KALA III PERSALINAN - Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Anemia in pregnancy if Hb levels below 11 g/dl during pregnancy, especially in the second trimester. One of the Impact of anemia is a disturbance of uterine contractions during labor. Weak contraction of the uterus can cause the duration of placental expenditure in the third stage of labor. The release of the placenta over 30 minutes causes postpartum hemorrhage which results in maternal death. The purpose of this study was to determine the effect of Hb level with the duration of placental expenditure in the third stage of labor. This research was an analytic research with correlation study with cross sectional approach. The data were collected by observation. The study population was maternal mothers in the district of Banyumas period of February-April 2017. Sampling technique was accidentally sampled until the sample quota was fulfilled. The sample criteria were maternal women vaginally, not given uterotonic other than in the first minute after the baby was born. Univariate analysis to know the frequency distribution of each variable of Hb level and length of placental expenditure. The bivariate analysis used a simple linear regression test. The result of research is normal distributed data. The mean of the variable Hb level value is 10.9 and the standard deviation is 0.96. the mean of the third stage of delivery value is 12.39 and the standard deviation 2.5. Result of significance value 0.012 less than 0.05 which means Ho rejected. There is an influence between Hb levels on the duration of the third stage of labor. Keywords: Hb, length of placenta expenditure